Drug delivery systems for oral disease applications (Journal of Applied Oral Science, 2022)
There are many restrictions on topical medications for the oral cavity. Various factors affect the topical application of drugs in the oral cavity, an open and complex environment. The complex physical and chemical environment of the oral cavity, such as saliva and food, will influence the effect of free drugs. Therefore, drug delivery systems have served as supporting structures or as carriers loading active ingredients, such as antimicrobial agents and growth factors (GFs), to promote antibacterial properties, tissue regeneration, and engineering for drug diffusion. These drug delivery systems are considered in the prevention and treatment of dental caries, periodontal disease, periapical disease, the delivery of anesthetic drugs, etc. These carrier materials are designed in different ways for clinical application, including nanoparticles, hydrogels, nanofibers, films, and scaffolds. This review aimed to summarize the advantages and disadvantages of different carrier materials. We discuss synthesis methods and their application scope to provide new perspectives for the development and preparation of more favorable and effective local oral drug delivery systems.